2017
DOI: 10.1016/j.cortex.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

The use of metacognitive strategies to decrease false memories in source monitoring in patients with mild cognitive impairment

Abstract: Patients with amnestic mild cognitive impairment (MCI) and Alzheimer's disease (AD) often demonstrate high rates of false memories, leading to stressful and frustrating situations for both patients and caregivers in everyday life. Sometimes these false memories are due to failures in monitoring the source of the information. In the current study, we examined interventions aimed to enhance the use of the metacognitive "recall-to-reject" memory strategy. Such interventions could improve source memory and decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…Patients with MCI-AD tended to perform in the intermediate range, in terms of both true and false memory, between patients with AD and healthy older controls across studies. Notably, patients with MCI-AD could generally apply cognitive strategies in order to improve their memory discrimination across studies, suggesting that while their hippocampal memory abilities may be impacted by AD, they still retained other cognitive abilities (e.g., executive functions), allowing them to successfully use cognitive strategies to improve their performance on memory tests, occasionally to a level similar to that of healthy controls (Brueckner & Moritz, 2009; Deason et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with MCI-AD tended to perform in the intermediate range, in terms of both true and false memory, between patients with AD and healthy older controls across studies. Notably, patients with MCI-AD could generally apply cognitive strategies in order to improve their memory discrimination across studies, suggesting that while their hippocampal memory abilities may be impacted by AD, they still retained other cognitive abilities (e.g., executive functions), allowing them to successfully use cognitive strategies to improve their performance on memory tests, occasionally to a level similar to that of healthy controls (Brueckner & Moritz, 2009; Deason et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, in a recent study, Deason, Nadkarni, and colleagues (2017) found that using a metacognitive strategy that enhanced recall-to-reject monitoring reduced false memories in patients with mild cognitive impairment. In their study, patients with MCI-AD and healthy older adults were presented with a simulated trip to the grocery store where they first studied items in the cupboard (viewed as pictures), then they studied items on their shopping list (viewed as words), and subsequently were tested on a mixture of old (both items from their cupboard and shopping list) and new pictures.…”
Section: Strategies To Reduce False Memoriesmentioning
confidence: 96%
See 2 more Smart Citations
“…This work established that many AD patients' false memories were related to the fact that they could remember the general idea, meaning, or gist of an event, but not the specific details (Budson, Daffner, Desikan, & Schacter, 2000). Part of their difficulty with false memories was related to the fact that patients have an abnormal sense of familiarity for things that were actually new (Deason et al, 2017).…”
Section: Introductionmentioning
confidence: 85%